Gagasan-Gagasan Baru dalam Pendidikan yang Menumbuhkan Sikap Kritis - Samsu Alam; Kasful Anwar US; Sya'roni Sya'roni (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
This research discusses new ideas in education that foster critical attitudes with the aim of knowing the benefits of critical thinking and knowing the steps in critical thinking. Given the importance of critical thinking in students, teachers are obliged to develop students' critical thinking skills. To develop critical thinking in students cannot be taught through the lecture method, because critical thinking is an active process. The learning carried out is student-centered. Intellectual skills from critical thinking including analytical thinking, synthetic thinking, reflective thinking, and so on must be learned through actualization of performance.Critical thinking skills are a demand in learning with the 2013 Curriculum. Critical thinking skills in students do not come by themselves, critical thinking skills in students are obtained through innovative activities of teachers. With the steps as above, the ability to think critically will grow and develop in students. To realize this, teachers are obliged to develop teachers' paedagogic and professional competencies for mastery of learning method strategies that stimulate the growth and development of critical thinking in students.